Measurement of Liquid Sheet using Laser Tagging Method by Photochromic Dye - Nurrina, Rosli; Amagai, Kenji (Springer, 2014)
Liquid atomization system has been extensively applied as the most significant process in many industrial fields. In the internal combustion engine, the combustion phenomenon is strongly influenced by the spray characteristics of the fuel given by the atomization process. In order to completely understand the whole atomization process, a detail investigation of relations between the liquid jet characteristics and the breakup phenomenon is required. In this study, a non-intrusive method called as laser tagging method by photochromic dye has been developed with aim to study the breakup process of liquid sheet in detail, covering from the behavior in film until disintegrated into ligament and droplets. The laser tagging method by photochromic dye is based on a shift in the absorption spectrum of photochromic dye molecules tagged by ultraviolet laser. The shift results a color change at the tagged region of liquid containing the dye. In this study, the motions of the dye traces were analyzed as the liquid surface velocity. As a result, liquid sheet was found to keep its velocity constantly in film before suddenly increase around broken point. However, it then decreased after broken into droplets. By forming a set of four points of dye traces on the liquid sheet, the change of relative position of the set enabled the measurement of deformation and rotational motion of the liquid sheet. As a result, the normal strain of the liquid sheet parallel to the flow direction depended on the flow behavior of ligament formation.